1994
DOI: 10.7863/jum.1994.13.11.835
|View full text |Cite
|
Sign up to set email alerts
|

Gray scale and color flow Doppler characterization of uterine tumors.

Abstract: The aim of this study was to investigate gray scale and color flow characteristics of a group of patients with a suspected uterine pathologic condition. One hundred and twenty-two consecutive patients at the Women's Cancer Center, University of Minnesota, undergoing transvaginal sonography and color flow Doppler imaging for suspected uterine corpus abnormality made up the study group. After gray scale morphologic assessment, color flow Doppler imaging of the tumor and uterus was performed, including the ipsila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Some studies suggest that transvaginal ultrasound scanning in combination with color flow Doppler may assist in the diagnosis of endometrial cancer, as blood flow is increased in malignancies (28)(29)(30)(31). However, increased blood flow has also been reported in benign conditions and results are conflicting whether Doppler sonography improves diagnosis of premalignant and malignant endometrial lesions (32)(33)(34)(35).…”
Section: Transvaginal Ultrasound Scanningmentioning
confidence: 99%
“…Some studies suggest that transvaginal ultrasound scanning in combination with color flow Doppler may assist in the diagnosis of endometrial cancer, as blood flow is increased in malignancies (28)(29)(30)(31). However, increased blood flow has also been reported in benign conditions and results are conflicting whether Doppler sonography improves diagnosis of premalignant and malignant endometrial lesions (32)(33)(34)(35).…”
Section: Transvaginal Ultrasound Scanningmentioning
confidence: 99%
“…These findings are consistent with prior studies indicating endometrial flow characteristics are not sufficiently sensitive, specific, or predictive to be used alone as sole criteria for prediction of malignancy. 6,22 Kurjak et al 23 demonstrated tumoral blood flow to be present in 91% of endometrial carcinomas, a much higher rate than in our experience, possibly related to sample size differences, differences in the criteria or techniques used, as well as their utilization of a gold standard of a hysterectomy specimen being the only specimen sampled in every case.…”
Section: Discussionmentioning
confidence: 52%
“…Numerous studies have now been published on CFD assessment of gynecologic tumors (5,6,9,12–19) . There is little doubt that the neovascularization associated with malignancy can be visualized by CFD.…”
Section: Discussionmentioning
confidence: 99%
“…The role of color flow Doppler in gynecologic tumor detection has been extensively studied. Tumor sites receiving most attention include the ovary and uterine corpus, while little has been published on cervical tumors (8–10) .…”
mentioning
confidence: 99%